Acoustic article and method
Patent Information
- Application Number
- JP2021562959
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-25
- Filing Date
- 2020-04-13
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2040-04-13
Smart Images

Figure 0007645814000029 
Figure 0007645814000030 
Figure 0007645814000031
Abstract
Description
[Technical field]
[0001] Described herein are acoustic articles suitable for use in thermal and acoustic insulation. The provided acoustic articles may be particularly suitable for reducing noise in automotive and aerospace applications. [Background technology]
[0002] Customer demands for faster, safer, quieter and more spacious vehicles continue to drive improvements in automotive and aerospace technology. Using conventional techniques, such improvements tend to increase vehicle weight and therefore reduce fuel economy. Lightweight solutions are available, but come with offsetting factors such as cost, complexity and manufacturing challenges. Developing such solutions can be a technical challenge, as measures taken to reduce weight often compromise performance in other areas.
[0003] Acoustic absorbers used in vehicles to combat noise, vibration, and harshness are representative of examples where such trade-offs appear. To improve fuel efficiency, automotive and aerospace manufacturers have replaced many heavy steel components with lighter materials such as aluminum and plastic. However, as vehicle structures become lighter, noise tends to become more difficult to mitigate due to the law of mass, which states that the sound insulation of solid elements generally increases by about 5 dB for every doubling of mass. Thus, lighter materials are typically at a disadvantage compared to heavier materials.
[0004] Conventional acoustic absorber materials include felt, foam, fiberglass, and polyester materials. These materials are generally provided in large thicknesses so that they are effective at absorbing airborne noise over a wide range of frequencies. This has the effect of making the absorber bulky, but reduces the cabin space available to the vehicle occupants. Summary of the Invention
[0005] In working towards improved acoustic solutions, it is recognized that noise can come from a variety of sources. Some noise comes from structural vibration, which causes sound energy to propagate and travel through the air, creating airborne noise. Structural vibration is traditionally controlled using damping materials made from heavy, viscous materials. Other types of airborne noise can come directly, such as from the wind or the vehicle's powertrain. Traditionally, airborne noise is controlled by using soft, pliable materials, such as fibrous wadding or foam, to absorb the sound energy.
[0006] Dense viscous materials have ideal properties for acoustic absorbers, but add significant weight to the vehicle. Furthermore, the size requirements for such materials can be significant. The performance of conventional acoustic absorbers can be estimated by comparing the magnitude of the sound waves with the thickness of the absorber. To be effective at absorbing low frequencies, these acoustic absorbers often need to have a thickness of at least about 10% of the wavelength of the incoming sound waves.
[0007] This is problematic because in some applications there may be geometric and / or volumetric constraints defined by the space in which the acoustic absorber is to be installed. These constraints may be encountered, for example, when shielding aerospace vehicles or automotive vehicles. To maximize cabin space, it is generally desirable to absorb sound in as thin a configuration as possible. However, due to the long wavelengths, low frequency noise tends to transmit easily through thin acoustic absorbers.
[0008] It has now been discovered that certain porous and / or fine organic and inorganic particles exhibit excellent absorption over a wide range of frequencies and can exhibit synergistic acoustic properties when incorporated into certain porous layers. This behavior has been observed in both polymeric and inorganic compositions, such as clay particles, diatomaceous earth, plant-based fillers, non-layered silicates, and non-expanded graphite. These porous and / or fine particles can be trapped in the interstices of a porous medium to produce a characteristic acoustic absorption profile. Such acoustic profile can be tailored through a combination of particle characteristics and how the acoustic profile is imparted within the porous medium.
[0009] This profile is the product of particle composition, particle surface area and particle size. Certain combinations of these materials can provide high levels of acoustic absorption over both high and low frequencies in thin layered configurations.
[0010] In a first aspect, an acoustic article is provided, the acoustic article comprising a porous layer and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 1 micrometer to 100 micrometers and a median particle size of 0.1 micrometer to 10 micrometers. 2 / g~100m 2 / g and a specific surface area of 100 MKS Rayls to 8000 MKS Rayls.
[0011] In a second aspect, an acoustic article is provided, comprising a porous layer and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 100 micrometers to 800 micrometers and a median particle size of 100 micrometers to 800 micrometers. 2 / g~800m 2 / g and a specific surface area of 100 MKS Rayls to 8000 MKS Rayls.
[0012] In a third aspect, an acoustic article is provided, comprising a porous layer; and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 100 micrometers to 1000 micrometers and a median particle size of 1 m 2 / g~100m 2 / g and a specific surface area of 100 MKS Rayls to 8000 MKS Rayls.
[0013] In a fourth aspect, an acoustic article is provided, comprising a porous layer; and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 m. 2 / g~800m 2 / g, and a non-uniform filler comprising diatomaceous earth, plant-based filler, unexpanded graphite, polyolefin foam, or a combination thereof, wherein the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls.
[0014] In a fifth aspect, there is provided a method of making an acoustic article, comprising: directly forming a nonwoven fibrous web; and delivering a nonuniform filler directly to the nonwoven fibrous web as the nonwoven fibrous web is formed, the nonuniform filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 micrometer to 10 micrometers. 2 / g~800m 2 and delivering a filler material comprising diatomaceous earth, plant-based filler, unexpanded graphite, polyolefin foam, or a combination thereof, the filler having a specific surface area of 100 MKS Rayls to 8000 MKS Rayls.
[0015] In a sixth aspect, there is provided a method of using an acoustic article comprising placing the acoustic article proximate to a surface to dampen vibrations of the surface.
[0016] In a seventh aspect, a method of using an acoustic article is provided that includes placing the acoustic article in proximity to an air cavity to absorb sound energy transmitted through the air cavity. [Brief description of the drawings]
[0017] [Figure 1] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Diagram 2] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Diagram 3] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 4] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Diagram 5] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 6] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 7] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 8] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 9] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 10] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 11] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 12] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 13] 1A-1D are side elevational views of single and multi-layer acoustic articles according to various embodiments. [Figure 14] 1 is a plot showing absorption coefficient as a function of frequency for various acoustic article embodiments.
[0018] Repeat use of reference characters in the specification and drawings is intended to represent the same or similar features or elements of the present disclosure. It is to be understood that those skilled in the art can devise numerous other modifications and embodiments that are within the scope and spirit of the principles of the present disclosure. The figures may not be drawn to scale.
[0019] definition As used herein, "Average" means number average unless otherwise specified.
[0020] "Copolymer" refers to a polymer made from repeating units of two or more different polymers, and includes random copolymers, block copolymers, and star (eg, dendritic) copolymers.
[0021] "Dimensionally stable" refers to a structure that substantially retains its shape (ie, does not sag) without the assistance of gravity.
[0022] "Die" means a processing assembly containing at least one orifice for use in polymer melt processing, including but not limited to meltblowing, and fiber extrusion processes.
[0023] "Discontinuous" when used with respect to a fiber or fibers means a fiber having a limited aspect ratio (eg, a ratio of length to diameter of, for example, less than 10,000).
[0024] By "entrapped" it is meant that the particles are dispersed and physically and / or adhesively held among the fibers of the web.
[0025] The "glass transition temperature" (T g "Temperature above which the polymer melts" refers to the temperature at which an amorphous polymer (or the amorphous regions of a semicrystalline polymer) undergoes a reversible transition from a hard, relatively brittle "glassy" state to a viscous or rubbery state with increasing temperature.
[0026] The "median fiber diameter" of the fibers in a nonwoven fibrous layer is determined by making one or more images of the fiber structure, for example using a scanning electron microscope, measuring the lateral dimensions of the fibers clearly visible in the one or more images to determine the total fiber diameter, and calculating the median fiber diameter based on the total fiber diameter.
[0027] By "nonwoven fibrous layer" is meant a plurality of fibers characterized by fiber entanglements or point bonds that form a sheet or mat in which the individual fibers or filaments overlap one another but exhibit a structure that is not discernible as in knitted fabrics.
[0028] "Oriented," when used with respect to fibers, means that at least a portion of the polymer molecules within the fiber are aligned with the longitudinal axis of the fiber, for example, by the drawing process as the fiber stream exits a die or by the use of an attenuation device.
[0029] "Particle" refers to separate pieces or individual portions of a material in finely divided form (i.e., primary particles), or aggregates thereof. Primary particles can include flakes, powders, and fibers, and may agglomerate, physically interlock, electrostatically associate, or otherwise associate to form aggregates. In certain instances, particles in the form of aggregates of individual particles may be formed, as described in U.S. Pat. No. 5,332,426 (Tang et al.).
[0030] By "polymer" is meant a relatively high molecular weight material having a molecular weight of at least 10,000 g / mol.
[0031] "Porous" means containing holes or voids.
[0032] "Shrinkage" refers to the reduction in dimensions of a fibrous nonwoven layer after heating to 150°C for 7 days based on the test method described in U.S. Patent Application Publication No. 2016 / 0298266 (Zillig et al.).
[0033] "Size" refers to the longest dimension of a given object or surface.
[0034] By "substantially" it is meant a majority or majority, such as an amount of at least 50%, 60, 70, 80, 90, 95, 96, 97, 98, 99, 99.5, 99.9, 99.99, or 99.999%, or 100%. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0035] As used herein, the terms "preferred" and "preferably" refer to embodiments described herein that may offer certain advantages, under certain circumstances, although other embodiments may also be preferred, under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are not useful, or is not intended to exclude other embodiments from the scope of the invention.
[0036] As used in this specification and the appended claims, the singular forms "a," "an," and "the" are intended to include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to an element followed by "a" or "the" may include one or more of the element and equivalents thereof known to those skilled in the art. Furthermore, the term "and / or" refers to one or all of the listed elements or a combination of any two or more of the listed elements.
[0037] It should be noted that the term "comprises" and variations thereof do not have a limiting meaning when these terms appear in the accompanying description. Furthermore, "a", "an", "the", "at least one" and "one or more" are used interchangeably herein. Relative terms such as left, right, front, rear, top, bottom, side, above, below, horizontal, vertical, etc. may be used herein, when taken from the perspective seen in a particular figure. However, these terms are used merely for ease of description and in no way limit the scope of the invention.
[0038] Throughout this specification, reference to "one embodiment," "a particular embodiment," "one or more embodiments," or "an embodiment" means that a particular feature, structure, material, or characteristic described with respect to that embodiment is included in at least one embodiment of the invention. Thus, the appearances of phrases such as "in one or more embodiments," "in a particular embodiment," "in one embodiment," or "in an embodiment" in various places throughout this specification are not necessarily all referring to the same embodiment of the invention.
[0039] The present disclosure is directed to acoustic articles, assemblies and methods thereof that function as sound absorbers, vibration dampeners, and / or sound and thermal insulators. The acoustic articles and assemblies generally include one or more porous layers and one or more non-uniform fillers in contact with the one or more porous layers. Optionally, the acoustic articles and assemblies provided include one or more non-porous barrier layers, resonators, and / or air gaps adjacent to the one or more porous layers. The structural and functional characteristics of each of these components are described in the following subsections.
[0040] acoustic goods Exemplary acoustic articles are illustrated in Figures 1-13 and described below. These acoustic articles can be effective in addressing both noise and undesirable vibrations associated with a structure. In some embodiments, the acoustic articles can be placed on a substrate or proximate an air cavity to absorb sound energy transmitted through the substrate or air cavity, respectively. In other embodiments, the acoustic articles can be placed proximate a surface to dampen vibrations of the surface.
[0041] Damping applications include near-field damping applications. Near-field damping is a mechanism for dissipating vibrational energy of a structure by controlling both non-propagating and propagating waves generated by structural vibration near the surface of the structure (near-field region). In the near-field region, oscillatory and incompressible fluids flow parallel to the surface of the structure, and the intensity of these flows gradually decreases with increasing distance from the vibrating structure's surface. The intensity of the energy in this region can be significant, so dissipating the energy in this region can help reduce structural vibration.
[0042] The near field can be defined as 30 centimeters to 0 centimeters, 15 centimeters to 0 centimeters, 10 centimeters to 0 centimeters, 8 centimeters to 0 centimeters, or 5 centimeters to 0 centimeters relative to the surface of a given substrate (or structure), where "0 centimeters" is defined as being at the surface of the substrate.
[0043] Further details regarding near-field damping can be found in Nicholas N. Kim, Seungkyu Lee, J. Stuart Bolton, Sean Hollands and Taewook Yoo, Structural damping by the use of fibrous materials, SAE Technical Paper, 2015-01-2239, 2015.
[0044] As shown in these figures, useful acoustic articles include both single layer and multi-layer configurations, and it should be understood that unless specifically indicated otherwise, one or more additional layers or surface treatments may be present on any major surface of a given acoustic article, or between layers of an otherwise adjacent acoustic article.
[0045] 1 illustrates a single layer acoustic article, hereinafter referred to by the numeral 100. Article 100 includes a porous layer 102 and a plurality of non-uniform fillers 104 dispersed therein. In this embodiment, non-uniform fillers 104 are uniformly dispersed within porous layer 102 throughout its thickness, as shown.
[0046] For purposes of example, the porous layer 102 is depicted here as a fibrous nonwoven layer composed of a plurality of fibers, although other types of porous layers (e.g., open cell foam, particulate bed) can also be used. Useful porous layers are described in more detail in another subsection below entitled "Porous Layers."
[0047] A non-uniform filler 104 having desirable acoustic properties is entrapped within a plurality of fibers of the porous layer 102. The non-uniform filler 104 may be present in an amount of 1% to 99%, 10% to 90%, 15% to 85%, 20% to 80% by weight, or in some embodiments, less than, equal to, or greater than 1%, 2, 3, 4, 5, 7, 10, 12, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 97, 98, or 99% by weight based on the combined weight of the porous layer 102 and the non-uniform filler 104.
[0048] Examples of non-uniform fillers that provide acoustic benefits include porous and / or finely divided fillers such as clays, diatomaceous earth, graphite, glass bubbles, porous polymeric fillers, non-layered silicates, vegetable-based fillers, and combinations thereof. A detailed description of these non-uniform fillers is provided in a later subsection entitled "Heterogeneous Fillers."
[0049] The non-uniform filler 104 within the porous layer 102 can affect the average fiber-to-fiber spacing within the non-woven fibrous structure of the porous layer 102. The extent to which this occurs depends, for example, on the particle size of the non-uniform filler 104 and the loading of the non-uniform filler 104 within the porous layer 102. The porous layer 102 may have an average fiber-to-fiber spacing of 0 micrometers to 1000 micrometers, 10 micrometers to 500 micrometers, 20 micrometers to 300 micrometers, or in some embodiments, may have an average fiber-to-fiber spacing less than, equal to, or greater than 0 micrometers, 1, 2, 3, 4, 5, 7, 10, 11, 12, 15, 17, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 110, 120, 150, 170, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, or 1000 micrometers.
[0050] Conversely, non-uniform filler 104 within acoustic article 100 has inter-particle (ie, particle-to-particle) spacing that depends, at least in part, on both its fill level and the structural properties of porous layer 102 . The non-uniform filler 104 may have an average interparticle spacing of 20 micrometers to 4000 micrometers, 50 micrometers to 2000 micrometers, 100 micrometers to 1000 micrometers, or in some embodiments, may have an average interparticle spacing less than, equal to, or greater than 20 micrometers, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 110, 120, 150, 170, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, 1000, 1100, 1200, 1500, 1700, 2000, 2500, 3000, 3500, or 4000 micrometers.
[0051] The average fiber-to-fiber, particle-to-fiber and particle-to-particle spacings can be obtained using X-ray microtomography, a non-destructive 3D imaging technique in which the imaging mechanism is the absorption of X-rays by components of the sample under examination. An X-ray source irradiates the sample and a detection system collects 2D X-ray images projected at distinct angular positions as the sample is rotated.
[0052] The collection of projected 2D images is captured through a process known as reconstruction to generate a stack of 2D slice images along the axis of rotation of the sample. The reconstructed 2D slice images can be examined individually as a series of images or used collectively to generate a 3D volume containing the examined sample. Measurements can be performed, for example, using a Skyscan 1172 (Bruker microCT, Kontich, Belgium) X-ray microtomography scanner at a suitable resolution (e.g., 1 micrometer to 3 micrometers) and X-ray source settings of 40 kV and 250 μA.
[0053] The reconstructed image can then be processed to isolate the location of particles and fibers within the scanned specimen. A grayscale threshold can isolate particles from low density material in the porous layer, as well as isolate particles and fibers from low density noise in the data set. Processing, such as with CT Analyzer software (v 1.16.4 Bruker microCT, Kontich, Belgium), can be performed to obtain the average particle-to-particle spacing, average particle-to-fiber spacing, and average fiber-to-fiber spacing.
[0054] The desired thickness of the porous layer 102 is highly application dependent and therefore need not be particularly limited. The porous layer 102 may have a total thickness of 1 micrometer to 10 centimeters, 30 micrometers to 1 centimeter, 50 micrometers to 5000 millimeters, or in some embodiments may have a total thickness less than, equal to, or greater than 1 micrometer, 2, 5, 10, 20, 30, 40, 50, 100, 200, 500 micrometers, 1 millimeter, 2, 3, 4, 5, 7, 10, 20, 50, 70, or 100 millimeters.
[0055] Advantageously, the combination of porous layer 102 and non-uniform filler 104 can significantly enhance acoustic absorption of low sound frequencies, such as sound frequencies between 50 Hz and 500 Hz, while preserving acoustic absorption of higher sound frequencies above 500 Hz.
[0056] In some embodiments, the addition of non-uniform filler can substantially increase the acoustic absorption of the acoustic article over sound frequencies less than, equal to, or greater than 50 Hz, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 105, 110, 115, 120, 125, 130, 135, 140, 145, 150, 155, 160, 165, 170, 175, 180, 185, 190, 195, 200, 210, 220, 230, 240, 250, 260, 270, 280, 290, 300, 400, 500, 700, 1000, 2000, 3000, 4000, 5000, 7000, or 10,000 Hz.
[0057] 2 shows an article 200 according to a dual layer embodiment, comprised of a first porous layer 202 containing a non-uniform filler 204 and a second porous layer 206 not containing the non-uniform filler 204. As shown, the second porous layer 206 extends throughout and is in direct contact with the first porous layer 202. The first porous layer 202 can have similar characteristics as the porous layer 102, previously described with respect to FIG.
[0058] Other embodiments are possible. For example, the heterogeneous filler may be only partially trapped in the first porous layer, with some heterogeneous filler present outside of this layer. In another embodiment, essentially the heterogeneous filler is not trapped in the first porous layer, and essentially all of the heterogeneous filler is present in a particulate bed of heterogeneous filler trapped between the first and second porous layers, both of which are unfilled.
[0059] 2, the second porous layer 206 has a thickness significantly greater than the thickness of the first porous layer 202. Depending on the nature of the noise to be mitigated, it may be advantageous for the first porous layer 202 to have a thickness significantly greater than the thickness of the second porous layer 206. One porous layer may have a thickness less than, equal to, or greater than 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, 150%, 200%, 250%, 300%, 400%, 500%, 600%, 700%, 800%, 900%, or 1000% of the thickness of the other porous layer.
[0060] One or more additional layers may be disposed between these layers, and the additional layers may extend across the entirety of the major exterior-facing surfaces of the first porous layer 202 and the second porous layer 206. An example of such a configuration is shown in Figure 3, which depicts an article 300 having three porous layers, where the first porous layer 302 and the third porous layer 308 are unfilled, and the second porous layer 304 is filled and sandwiched between the two aforementioned layers.
[0061] In multi-layer configurations (e.g., articles 200, 300 of Figures 2 and 3), a non-filled porous layer can improve the low frequency performance of the overall acoustic article. To achieve a high degree of acoustic absorption, the acoustic impedance of the article can be close to the characteristic impedance of the surrounding fluid. When the surrounding fluid is air, the characteristic impedance is the product of the density and speed of sound of the air medium. Thus, the porous layer can help match the acoustic impedance of the multi-layer article to the characteristic impedance of the surrounding medium.
[0062] In the case of a normally incident plane wave, the specific acoustic impedance at the surface of the material, z surf can be written in terms of thickness L as
number
number
[0063] The reduction in sound velocity can improve low frequency performance without increasing the thickness of the material. At the surface of the material against a rigid wall, both the particle velocities v and x approach zero, resulting in an infinite surface impedance. Based on the above relationship, it is speculated that non-uniform fillers in the porous layer can help to lower the frequency at which the surface of the material provides zero acoustic impedance by changing the wavelength in the material and providing a pressure reduction effect. In some embodiments, the addition of non-uniform fillers can also reduce the reflection of sound waves within the acoustic article. With the reduced pressure, the acoustic impedance also decreases, allowing some of the sound to pass through and helping to capture more sound energy within the overall acoustic article, thereby improving noise dissipation and therefore barrier performance.
[0064] In the above embodiments, the non-uniform filler is substantially decoupled from each other and from any porous layers. That is, the particles of the non-uniform filler are not physically attached to each other and can move or oscillate, at least to a limited extent, independently of the surrounding structure. In these examples, the trapped particles can move and vibrate within the fibers of the nonwoven material largely independent of the fibers themselves.
[0065] Alternatively, at least a portion of the non-uniform filler may be physically bonded to the porous layer in which it is disposed. In some embodiments, these physical bonds are created by incorporating a binder (e.g., binder fibers) into the porous layer that can become tacky and adhere to the filler particles upon application of heat. To preserve the acoustic properties of the non-uniform filler, it is generally preferred that the binder not significantly flow into the pores of the filler particles.
[0066] It should be understood that further embodiments are possible in which the acoustic article is comprised of four, five, six, seven, or even more porous layers, with at least one porous layer containing or otherwise in contact with a non-uniform filler.
[0067] 4 shows a side view of another acoustic article 400 having a first porous layer 402 and a second porous layer 404, and a layer of non-uniform filler 420 disposed between the porous layers 402, 404. The porous layers 402, 404 and the non-uniform filler 420 are similar to the porous layers described with respect to FIGS. 1-3. In this embodiment, the porous layers 402, 404 not only contribute to the acoustic performance of the article 400, but can also serve to physically confine and secure the non-uniform filler 420 in the space between the porous layers 402, 404.
[0068] In this embodiment, the non-uniform filler 420 is not trapped within the porous layers 402, 404, but rather forms a particulate bed. The article 400 is also divided into a plurality of compartment chambers 430 by walls 432 to provide a quilt-like structure. The chambers 430 are disposed transversely relative to one another, with each chamber 430 including a first porous layer 402, a layer of non-uniform filler 420, and a second porous layer 404, as shown. Optionally, the chambers 430 can have a two-dimensional lattice configuration in plan view.
[0069] The walls 432 that separate the chambers 430 from one another need not be of limited composition and may be porous or non-porous. In a preferred embodiment, the walls 432 are fabricated from a flexible polymer membrane, scrim, or perforated film having low flow resistance. Advantageously, the walls 432 provide improved anchoring of the non-uniform filler 420 in the acoustic article 400, and may also improve acoustic performance by providing dissipation of grazing waves due to the presence of side boundaries within the article 400.
[0070] Further aspects of article 400 are described in co-pending International Patent Application PCT / US18 / 56671 (Lee et al.), filed October 19, 2018.
[0071] 5 shows an acoustic article 500 using a perforated film as the porous layer. The acoustic article 500 includes a non-uniform filler 520 trapped between a first perforated film 502 and a second perforated film 504. The films 502, 504 have a plurality of apertures 503, 505 (or through holes) extending through each of the perforated films 502, 504 along a direction perpendicular to the major surface of the article 500. Optionally, and as shown, the plurality of apertures 503, 505 are arranged in a two-dimensional pattern with regular center-to-center spacing between adjacent apertures.
[0072] In the illustrated embodiment, film 504 is significantly thicker than film 502. Additionally, aperture 503 is generally cylindrical, while aperture 505 has tapered sidewalls, creating an opening having a generally conical shape. As shown in FIG. 5, non-uniform filler 520 resides within the generally conical aperture and is held immobile between films 502 and 504 because the particles of non-uniform filler 520 are significantly larger than the minimum width of apertures 503, 505. In an alternative embodiment, the non-uniform filler may be captured between a pair of symmetrically positioned perforated films.
[0073] The films 502, 504 can be joined together by any known method. They can be attached using adhesives, thermal lamination, and / or mechanical interlocking. Either of the films 502, 504 can also be joined to the previously described fibrous nonwoven layer using any of these methods. In some embodiments, the fibrous nonwoven layer contains adhesive polymer fibers that aid in attachment to a non-uniform filler, a perforated film, or another fibrous nonwoven layer. Suitable adhesive fibers include, for example, adhesive fibers made from styrene-isoprene-styrene or polyethylene / polypropylene copolymers.
[0074] In another embodiment, an acoustic article may be provided in which one of the films 502, 504 is omitted.
[0075] In yet another embodiment, the perforated film 502 can be replaced with another porous layer, such as a resistive scrim. The resistive scrim is a thin porous layer that exhibits high flow resistance (e.g., up to 2000 MKS Rayls). In some embodiments, the resistive scrim is a nonwoven fibrous web having a thickness of less than 5000 micrometers and has negligible bending stiffness.
[0076] Acoustic performance can be further enhanced, especially at low frequencies, by including a resistive layer, such as a resistive scrim. The resistive layer can have a flow resistance of 10 MKS Rayls to 8000 MKS Rayls, 20 MKS Rayls to 3000 MKS Rayls, or 50 MKS Rayls to 1000 MKS Rayls. In some embodiments, the flow resistance through the resistance layer is less than, equal to, or greater than 10 MKS Rayls, 20, 30, 40, 50, 70, 100, 200, 300, 400, 500, 600, 700, 1000, 1100, 1200, 1500, 1700, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, or 8000 MKS Rayls.
[0077] The resistive layer may have a thickness of 1 micrometer to 10 centimeters, 30 micrometers to 1 centimeter, 50 micrometers to 5000 micrometers, or in some embodiments may have a thickness less than, equal to, or greater than 10 micrometers, 20, 30, 40, 50, 70, 100, 200, 500, 1 millimeter, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 millimeters (10 centimeters).
[0078] 6 shows an acoustic article 600 in which the porous layers have a heterogeneous loading of non-uniform filler. In this configuration, the article 600 has a first porous layer 602 with a high relative loading of non-uniform filler 604, a second porous layer 606 with a low relative loading of non-uniform filler 604', and a third porous layer 608 that is devoid of any non-uniform filler. The non-uniform fillers 604, 604' may or may not have the same composition. The non-uniform fillers 604, 604' may or may not have the same median particle size. Similarly, the porous layers 602, 606, 608 are intended here to be general and therefore may or may not have the same composition and structure.
[0079] When the non-uniform fillers 604, 604' have the same composition and particle size, the article 600 has distinct layers with a gradually decreasing density from the top of the article 600 to the bottom of the article 600, as shown in Figure 6. Advantages of this configuration include design freedom and customizability, reduced cost, and tunability, which can enhance acoustic absorption over certain frequencies as needed.
[0080] 7 shows an acoustic article 700 in which a monolithic porous layer 702 contains two distinct particle size non-uniform fillers 704. The non-uniform fillers 704 may have a bimodal distribution of particle sizes as shown here, or some other multimodal distribution. Alternatively, the non-uniform fillers 704 may have a unimodal but broad distribution. By mixing non-uniform fillers with different particle sizes together, the total loading of the filler can be increased because the smaller particles can occupy the voids created by the larger particles.
[0081] 8 shows an acoustic article 800 that employs a porous layer 802 that contains a density gradient of non-uniform filler 804. As shown, the density is highest near the top major surface and lowest near the bottom major surface.
[0082] 9 shows an acoustic article 900 having a two-layer configuration, comprised of a first porous layer 902 containing a plurality of first non-uniform fillers 904 and a second porous layer 906 containing a plurality of second non-uniform fillers 908. The porous layers 902, 906 are in flat contact with one another and may be made of the same or different materials. The non-uniform fillers 908 have a median particle size larger than the size of the non-uniform fillers 904, as shown.
[0083] Figures 10-13 illustrate further variations and combinations of the acoustic layers previously presented. For example, Figure 10 shows an acoustic article 1000 in which a first porous layer 1002 is a perforated film and is disposed on a second porous layer 1004 composed of a nonwoven fibrous web containing a plurality of non-uniform fillers 1006. The layers 1002, 1004 are backed by a third porous layer 1008, which is unfilled and also made from a nonwoven fibrous web. As indicated above, in these configurations, the acoustic behavior of the overall acoustic article can be tailored to a particular application. Such acoustic behavior may include a combination of reflection, absorption, and noise cancellation.
[0084] 11 shows an acoustic article 1100 that has some similarities to article 1000, but includes a first porous layer 1102 that is a particle-filled perforated film. The perforated film contains a plurality of perforations 1106 that contain a non-uniform filler 1104, as shown. Underlying the first porous layer 1102 are a second porous layer 1108 and a third porous layer 1110 that are generally similar to those described with respect to article 1000 in FIG.
[0085] 12 shows an acoustic article 1200 that is also similar to the article 1000 in FIG. 10 except that it includes a fourth porous layer 1208 that extends throughout the first porous layer 1202, the second porous layer 1204, and the third porous layer 1206, with a non-uniform filler 1207 trapped in the second porous layer 1204. The fourth porous layer 1208 is a perforated film that does not contain or is not in direct contact with the non-uniform filler 1207.
[0086] 13 shows an acoustic article 1300 coupled to a substrate 1350. The acoustic article 1300 has a first porous layer 1302 and a second porous layer 1304 somewhat similar to those of the acoustic article 500 in FIG. 5. A non-uniform filler 1306 is present in the second porous layer 1304 and is mechanically held within the perforations of the second porous layer 1304 by the first porous layer 1302. A third porous layer 1305 extending throughout and in direct contact with the second porous layer 1304 is comprised of a nonwoven fibrous web and is further bonded to the substrate 1350.
[0087] Substrates include structural components such as automotive or aircraft parts and building substrates. Structural examples include molded panels (e.g., door panels), aircraft frames, in-wall insulation, and integral ducts. Substrates can also include adjacent components to these structural examples, such as carpets, trunk liners, fender liners, dashboard coverings, floor trusses, wall panels, and duct insulation. In some cases, the substrate can be spaced apart from the acoustic article, such as in hood liners, headliners, aircraft panels, drapes, and ceiling tiles. Further applications of these materials include filtration media, surgical drapes and wipes, liquid and gas filters, clothing, blankets, furniture, transportation (e.g., for aircraft, rotorcraft, trains, and automobile vehicles), electronics (e.g., for televisions, computers, servers, data storage devices, and power supplies), air volume control steering systems, interior trim, and personal protective equipment.
[0088] In the acoustic articles described above, the solidity of a given layer depends on the degree to which the non-uniform filler is loaded into the layer. Solidity can be increased if the non-uniform filler particles occupy spaces that would otherwise remain as voids in the porous layer. However, solidity can also be decreased if the inclusion of non-uniform filler expands the structure of the porous layer and creates voids that would not otherwise exist.
[0089] As used herein, solidity is a property that is inversely related to density and is specific to the permeability and porosity of the web (the formula for solidity is provided in the Examples). Low solidity corresponds to high permeability and high porosity. The provided porous layers, when filled with non-uniform fillers, can have a solidity of 5 percent to 40 percent, 8 percent to 35 percent, 10 percent to 30 percent, or in some embodiments, can have a solidity of less than, equal to, or greater than 5 percent, 6, 7, 8, 9, 10, 11, 12, 15, 17, 20, 22, 25, 27, 30, 32, 25, 37, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, or 95 percent. The provided porous layer, in its unfilled form, can have a solidity less than, equal to, or greater than 5 percent, 6, 7, 8, 9, 10, 11, 12, 15, 17, 20, 22, 25, 27, 30, 32, 25, 37, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, or 95 percent.
[0090] Any of the aforementioned acoustic articles may further include one or more air gaps enclosed between adjacent layers. The air gaps can act as resonant chambers and enhance transmission loss through the acoustic article at certain frequencies. The air gaps can act as acoustic resonators based on the quarter-wave theory. According to this theory, peak acoustic absorption occurs at a frequency that represents a quarter-wavelength of the thickness of the acoustic layer. With larger air gaps, the peak acoustic absorption shifts to lower frequencies. For example, an air gap that is 5 centimeters thick may have a peak absorption at 1600 Hz, while an air gap that is 10 cm thick may have a peak absorption that occurs at 800 Hz.
[0091] The air gap can have any thickness that enables it to function as an acoustic resonator. Typically, depending on the acoustic frequencies of interest, the air gap may have a thickness of 10 micrometers to 10 centimeters, 500 micrometers to 5 centimeters, 1 millimeter to 3 centimeters, or in some embodiments, may have a thickness less than, equal to, or greater than 10 micrometers, 20, 30, 40, 50, 70, 100, 200, 500, 1 millimeter, 2, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100 millimeters (10 centimeters).
[0092] The provided acoustic articles can also include a layer containing a plurality of Helmholtz resonators in contact with the porous layer, which can be disposed on either major surface of the acoustic article or can be disposed between otherwise adjacent layers within the acoustic article.
[0093] A Helmholtz resonator is essentially a small container filled with air, with an open port. The volume of air in the container has spring properties that allow the air to vibrate and dissipate sound energy at a certain frequency or range of frequencies. Helmholtz resonators can be arranged in a two-dimensional array that spans the entire major surface of the acoustic article. Although not intended to be limiting, examples of suitable Helmholtz resonators include those described, for example, in International Patent Application Publication No. WO2013169788 (Castiglione et al.).
[0094] Composite acoustic articles including Helmholtz resonators may have a relatively low density non-uniform filler. For example, less than 50% of the total void volume may be taken up by the non-uniform filler. The non-uniform filler particles may have non-uniform orientations and / or may be irregularly shaped. For example, asymmetric elongated particles may be present in the pores small end down, large end down, or in a transverse orientation. Each orientation produces a unique characteristic absorption. Because the acoustic articles provided contain a wide variety of different particle orientations within the porous layer, these articles can absorb over a wider frequency range than the Helmholtz resonator alone.
[0095] Figure 14 illustrates the broad spectrum of acoustic behavior that can be obtained by varying the particle size of the non-uniform filler. Five different acoustic articles, designated Types 1-5, are shown here in particulate bed configurations. It should be understood that similar acoustic behavior can be obtained by placing the same or similar non-uniform filler in other porous layers, including nonwoven fibrous layers and foams.
[0096] In this figure, the absorption coefficient is plotted as a function of frequency measured for the non-uniform fillers provided below. Type 1: Porous poly(divinylbenzene-maleic anhydride), diameter less than 250 micrometers Type 2: Silica gel, diameter 150 micrometers to 250 micrometers Type 3: Porous poly(divinylbenzene-maleic anhydride), diameter 250 micrometers to 420 micrometers Type 4: Porous poly(divinylbenzene-maleic anhydride), diameter 420 micrometers to 595 micrometers Type 5: Porous poly(divinylbenzene-maleic anhydride), diameter >595 micrometers
[0097] Porous Layer The provided acoustic article includes one or more porous layers. Useful porous layers include, but are not limited to, nonwoven fibrous layers, perforated films, particulate beds, and open-cell structures such as open-cell foams, fiberglass, nets, woven fabrics, and combinations thereof. Porous layers are generally permeable, allowing air or some other fluid to freely communicate between the opposing sides of the layer. Such layers may also be semi-permeable (partially but not entirely permeable along the thickness dimension) or impermeable.
[0098] Certain nonwoven fibrous layers can be effective sound absorbers even without non-uniform fillers. For example, nonwoven materials containing multiple fine fibers can be very effective at reducing high-pitched sounds frequencies. In this frequency regime, the surface area of the structure can promote viscous dissipation of noise, the process by which sound energy is converted into heat.
[0099] The nonwoven layer can be made from a wide variety of materials, including organic and inorganic materials. One inorganic fibrous nonwoven material is fiberglass. Fiberglass is generally made by melting silica and other minerals in a furnace and then extruding it through a spinneret containing small orifices to produce streams of molten glass. These streams are guided by a flow of hot air, cooled into fibers, and deposited on a conveyor belt, where the fibers intertwine with each other to produce a nonwoven fiberglass layer.
[0100] The polymeric nonwoven layer can be manufactured using a meltblowing process. Meltblown nonwoven fibrous layers can contain very fine fibers. In meltblown, one or more thermoplastic polymer streams are extruded through a die containing closely arranged orifices. These polymer streams are attenuated by converging streams of high-velocity hot air to form fine fibers that then collect on a surface to provide the meltblown nonwoven fibrous layer. Depending on the operating parameters selected, the collected fibers can be semi-continuous or essentially discontinuous.
[0101] The polymeric nonwoven layer can also be produced by a process known as melt spinning. In melt spinning, nonwoven fibers are extruded as filaments through a set of orifices, cooled, and solidified to form fibers. The filaments pass through an air space, which may contain a flow of moving air, to aid in cooling the filaments and passing through an attenuation (i.e., drawing) unit to at least partially draw the filaments. Fibers produced through the melt spinning process can be "spunbonded," whereby a web containing a set of melt spun fibers is collected as a fibrous web, which may optionally be subjected to one or more bonding operations to fuse the fibers together. Melt spun fibers are generally larger in diameter than meltblown fibers.
[0102] Suitable polymers for use in the meltblowing or melt spinning process include polyolefins such as polypropylene and polyethylene, polyesters, polyethylene terephthalate, polybutylene terephthalate, polyamides, polyurethanes, polybutenes, polylactic acid, polyphenylene sulfide, polysulfones, liquid crystal polymers, polyethylene-co-vinyl acetate, polyacrylonitrile, cyclic polyolefins, and copolymers and blends thereof.
[0103] The nonwoven fibers can be made from thermoplastic semicrystalline polymers such as semicrystalline polyesters. Useful polyesters include aliphatic polyesters. Nonwoven materials based on aliphatic polyester fibers can be particularly advantageous in resisting degradation or shrinkage in high temperature applications. This property can be achieved by producing nonwoven fibrous layers using a meltblowing process in which meltblown fibers exiting from a number of orifices are immediately subjected to a controlled air-heat treatment operation. The controlled air-heat treatment operation is carried out at a temperature below the melting temperature of a portion of the meltblown fibers for a time sufficient to achieve stress relaxation of at least a portion of the molecules of the portion of the fibers subjected to the controlled air-heat treatment operation. Details of air-heat treatment are described in U.S. Patent Application Publication No. 2016 / 0298266 (Zillig et al.).
[0104] For useful aliphatic polyesters, the molecular weight need not be particularly limited and may range from 15,000 g / mol to 6,000,000 g / mol, 20,000 g / mol to 2,000,000 g / mol, 40,000 g / mol to 1,000,000 g / mol, or in some embodiments, 15,000 g / mol, 20,000, 25,000, 30,000, 35,000, 40,000, 40,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 110,000, 120,000, 130,000, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 210,000, 220,000, 230,000, 240,000, 250,000, 260,000, 270,000, 280,000, 290,000, 300,000, 310,000, 320,000, 330,000, 340,000, 350,000, 360,000, 370,000, 380,000, 390,000, 400,000, 410,000, 420,000, 430,000, 440,000, 450, The value may be less than, equal to, or greater than 5,000, 50,000, 60,000, 70,000, 80,000, 90,000, 100,000, 200,000, 500,000, 700,000, 1,000,000, 2,000,000, 3,000,000, 4,000,000, 5,000,000, or 6,000,000 g / mol.
[0105] The fibers of the nonwoven fibrous layer can have any suitable diameter. The fibers may have a median fiber diameter of 0.1 micrometers to 10 micrometers, 0.3 micrometers to 6 micrometers, 0.3 micrometers to 3 micrometers, or in some embodiments, may have a median fiber diameter less than, equal to, or greater than 0.1 micrometers, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 22, 25, 27, 30, 32, 35, 37, 40, 42, 45, 47, 50, 53, 55, 57, or 60 micrometers.
[0106] Optionally, at least some of the fibers in the nonwoven fibrous layer are physically bonded to each other or to the nonuniform filler. Generally, this has the effect of increasing stiffness and / or strength to the acoustic article, which may be desirable in certain applications. Traditional bonding techniques include the use of heat and pressure applied in a point bonding process or by passing the nonwoven fibrous layer through a smooth calendar roll. However, such processes may cause deformation of the fibers or compaction of the web, which may or may not be desirable.
[0107] Alternatively, adhesion between the fibers or between the fibers and the non-uniform filler may be achieved by incorporating a binder into the nonwoven fibrous layer. In some embodiments, the binder is provided by a liquid or solid powder. In some embodiments, the binder is provided by short binder fibers, which may be injected into the polymer stream during the meltblowing process. The binder fibers have a melting temperature significantly lower than the melting temperature of the remaining structural fibers and act to secure the fibers together.
[0108] Other methods for bonding fibers together are taught, for example, in US Patent Application Publication No. 2008 / 0038976 (Berrigan et al.) and US Patent No. 7,279,440 (Berrigan et al.). In one technique, a web of collected fibers is exposed to a controlled heating and quenching operation that includes forcing the web through a gas stream heated to a temperature sufficient to soften the fibers and bond them together at the points where the fibers cross, where the heated stream is applied for only a short period of time to completely melt the fibers, and then immediately forcing the web through a gas stream at a temperature at least 50° C. lower than the heated stream to quench the fibers.
[0109] In some embodiments, the fiber polymer has a high glass transition temperature, which may be preferred if the acoustic article is to be used in a high temperature environment. Certain nonwoven fiber layers shrink significantly when heated to even moderate temperatures in subsequent processing or use, such as when used as an insulating material. Such shrinkage may be problematic for some applications when the meltblown fibers include thermoplastic polyesters or copolymers thereof, especially those that are semi-crystalline in nature.
[0110] In some embodiments, the nonwoven fibrous layer provided has at least one densified layer adjacent to a non-densified layer. Either or both of the densified and non-densified layers may be filled with non-uniform fillers. The densified layer can provide several potential advantages. If sufficiently dense, such a layer, when placed on the outermost surface of the acoustic article, can act as a barrier to prevent non-uniform filler particles from escaping the acoustic article. The densification of the nonwoven layer can also enhance structural integrity, provide dimensional stability, and mold the nonwoven layer into a three-dimensional shape. Advantageously, the molded acoustic article can be customized to fully utilize the space in which it is placed.
[0111] In some embodiments, the densified layer and adjacent non-densified layer are prepared from an initially monolithic nonwoven fibrous layer having uniform density, which is then subjected to heat and / or pressure to produce a densified layer on its outermost surface. Methods for producing densified layers on nonwoven fibrous webs, along with further options and advantages, are described in co-pending International Patent Application PCT / CN2017 / 101857 (You et al.).
[0112] In some embodiments, the densified layer has a uniform distribution of polymeric fibers throughout the layer. Alternatively, the distribution of polymeric fibers may vary across a major surface of the nonwoven fibrous layer. Such a configuration may be appropriate, for example, when the acoustic response is dependent on position along the major surface.
[0113] The median fiber diameter of the densified and non-densified portions of the nonwoven fibrous layer can be substantially maintained. The above processes generally allow the fibers to fuse together in the densified regions without significant melting of the fibers. In most instances, it is preferred to avoid melting of the fibers in order to preserve the acoustic benefits derived from the surface area of the densified layer of the nonwoven fibrous layer.
[0114] Other nonwoven fibrous layers that may be used in acoustic articles include recycled woven fibers, sometimes called shoddy. The recycled woven fibers can be formed into a nonwoven structure using an airlaid process, in which a wall of air blows the fibers onto a perforated collection drum with negative pressure on the inside of the drum. Air is pulled through the drum and the fibers collect on the outside of the drum and are removed as a web. Due to the turbulence of the air, the fibers are not in any ordered orientation and therefore can exhibit relatively uniform strength properties in all directions.
[0115] One or more additional fiber populations may be incorporated into the nonwoven fibrous layer. The distinction between the fiber populations may be based on, for example, composition, median fiber diameter, and / or median fiber length.
[0116] For example, the nonwoven fibrous layer may include a plurality of first fibers having a median diameter of up to 10 micrometers and a plurality of second fibers having a median diameter of at least 10 micrometers. It may be advantageous to have fibers of different diameters for a variety of reasons. The inclusion of thicker second fibers may improve the resilience, compression resistance, and help maintain the overall loft of the web of the nonwoven fibrous layer. The second fibers may be made from any of the polymeric materials previously described for the first fibers, and may be made from a meltblowing process or a melt spinning process.
[0117] In some embodiments, the second fibers are staple fibers intermingled with the first plurality of fibers. These staple fibers can be provided as crimped fibers to improve the overall bulk of the fibrous web. The staple fibers can include binder fibers that can be made from any of the polymer fibers described above. The structural fibers can include, but are not limited to, any of the polymer fibers described above, as well as inorganic fibers such as ceramic fibers, glass fibers, and metal fibers, and organic fibers such as cellulose fibers.
[0118] The first and second fibers can independently have any of the compositions, structures, and properties described above for nonwoven fibrous layers containing only a single population of fibers. Additional features and advantages of combinations of first and second fibers are described in U.S. Patent No. 8,906,815 (Moore et al.).
[0119] Nonwoven fibrous layers can provide a number of technical advantages, at least some of which are unexpected. One advantage comes from the surface area of the nonwoven fibrous layer. The retention of the surface area provided by fibers, combined with a non-uniform filler having a high surface area, can provide a high level of performance as an acoustic absorber, even in an acoustic material of relatively small weight (or thickness).
[0120] These nonwoven materials can also be made from fibrous materials that can withstand high temperatures that would cause traditional insulation materials to thermally degrade or fail. This makes them suitable for insulation in automotive and aerospace vehicle applications that typically operate in environments that are not only noisy but can also reach extreme temperatures. These materials can be very resilient, and can fill the available space in a given cavity by compressing and springing back. Finally, as mentioned above, these nonwoven fibrous layers can also be molded to fit the substrate or cavity in a given application, if molding is desired, which allows for easy installation by workers.
[0121] In some embodiments, the porous layer is made of a perforated film. A perforated film is made of a solid layer with a large number of perforations, i.e. through holes, extending through the solid layer. The perforations allow fluid communication between the air spaces on either side of the wall. A microperforated film is a perforated film with openings that are micrometers in diameter. These perforated films are generally made of polymeric materials, but can also be made of other materials, including metals.
[0122] Similar to nonwoven fibrous layers, perforated films can have configurations that allow them to absorb sound. Conceptually, air plugs exist within the perforations and act as mass components in a resonant system. These mass components vibrate within the perforations and dissipate sound energy through friction between the air plugs and the walls of the perforations. When a perforated film is placed adjacent to an air cavity, dissipation of sound energy can also occur through destructive interference at the entrance to the perforations with sound waves reflected from opposite directions back toward the perforations. Absorption of sound energy occurs with essentially zero net flow of fluid through the acoustic article.
[0123] The perforations can have suitable dimensions (e.g., perforation diameter, shape, and length) to obtain the desired acoustic performance over a given frequency range. Acoustic performance can be measured, for example, by reflecting sound off the perforated film and characterizing the reduction in acoustic intensity compared to the results from a control sample.
[0124] In the figures, the perforations are located across the entire surface of the perforated film, or the wall may be only partially perforated, i.e., perforated in some areas and not perforated in others.
[0125] Compared to other porous layers, perforated films can be relatively thin while retaining their acoustic absorption properties. Perforated films may have a total thickness of 1 micrometer to 2 millimeters, 30 micrometers to 1.5 millimeters, 50 micrometers to 1 millimeter, or in some embodiments, may have a total thickness less than, equal to, or greater than 1 micrometer, 2, 5, 10, 20, 30, 40, 50, 100, 200, 500, 700 micrometers, 1 millimeter, 1.1, 1.2, 1.5, 1.7, or 2 millimeters. In embodiments where thickness is not constrained, perforated slabs are used instead of perforated films, with the perforated slabs having thicknesses of up to 3 millimeters, 5, 10, 30, 50, 100, or even 200 millimeters.
[0126] The perforations can have a wide variety of shapes and sizes and can be produced by any of a variety of molding, cutting or punching operations. The cross-section of the perforations can be, for example, circular, square or hexagonal. In some embodiments, the perforations are constituted by an array of elongated slits.
[0127] As described in co-pending International Patent Application PCT / US18 / 56671 (Lee et al., see e.g., Figures 15a-c and related description), the perforations may have a uniform diameter along their length, although it is possible to use perforations having a frusto-conical, truncated pyramidal, or other shape with tapered sidewalls along at least some of their length. The degree to which the sidewalls taper may be selected to accommodate non-uniform filler within the perforations. Tapering the perforations also narrows one side of the opening, a feature that may help prevent non-uniform filler from leaking through the perforated film.
[0128] Optionally, and as shown in the figures, the perforations have a generally uniform spacing relative to one another. In that case, the perforations may be arranged in a two-dimensional grid pattern or a staggered pattern. The perforations may also be disposed in the wall in a randomized configuration where the locations of the perforations are irregular, but still, on a macroscopic scale, the perforations are evenly distributed throughout the wall.
[0129] In some embodiments, the perforations are of essentially uniform diameter throughout the wall. Alternatively, the perforations may have some distribution of diameters. In any case, the average minimum diameter of the perforations may be less than, equal to, or greater than 10 micrometers, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 110, 120, 150, 170, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, 1000, 1500, 2000, 2500, 3000, 4000, or 5000 micrometers. For clarity, the diameter of a non-circular hole is defined herein as the diameter of a circle that has an area equivalent to that of the non-circular hole in plan view.
[0130] The porosity of a perforated film is a dimensionless quantity that represents the fraction of a given volume that is not occupied by the film. In simplified terms, the perforations can be considered cylindrical, in which case the porosity is well approximated by the percentage of the surface area of the wall that is displaced by the perforations in plan view. In exemplary embodiments, the wall can have a porosity of 0.1% to 80%, 0.5% to 70%, or 0.5% to 60%. In some embodiments, the wall has a porosity less than, equal to, or greater than 0.1%, 0.2, 0.3, 0.4, 0.5, 0.7, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, or 80%.
[0131] The film material can have a modulus of elasticity (e.g., flexural modulus) suitably tailored to vibrate in response to incident acoustic waves having a relevant frequency. Localized vibration of the wall itself, together with the vibration of the air plugs in the perforations, can dissipate sound energy and enhance transmission losses through the acoustic article. The flexural modulus of the wall reflects its stiffness and also directly affects its acoustic transfer impedance.
[0132] In some embodiments, the film comprises a material having a flexural modulus of 0.2 GPa to 10 GPa, 0.2 GPa to 7 GPa, 0.2 GPa to 4 GPa, or in some embodiments, a material having a flexural modulus less than, equal to, or greater than the following values: 0.2 GPa, 0.3, 0.4, 0.5, 0.7, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 17, 20, 25, 30, 35, 40, 50, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, or 210 GPa.
[0133] Suitable thermoplastic polymers typically have a flexural modulus in the range of 0.2 GPa to 5 GPa. In some embodiments, the addition of fibers or other fillers can increase the flexural modulus of these materials to up to 20 GPa. Thermosetting polymers generally have a flexural modulus in the range of 5 GPa to 40 GPa. Useful polymers include polyolefins, polyesters, fluoropolymers, polylactic acid, polyphenylene sulfide, polyacrylates, polyvinyl chloride, polycarbonates, polyurethanes, and blends thereof.
[0134] Exemplary perforated film constructions, their methods of manufacture and acoustic performance characteristics are described in U.S. Pat. Nos. 6,617,002 (Wood), 6,977,109 (Wood) and 7,731,878 (Wood), 9,238,203 (Scheibner et al.), and U.S. Patent Application Publication No. 2005 / 0104245 (Wood).
[0135] In some embodiments, the porous layer is comprised of a particulate bed. The particulate bed may be made entirely of heterogeneous packing. Alternatively, the particulate bed may include at least some particles that are not heterogeneous packing. The particulate bed may include any of the heterogeneous packings described herein, zeolites, metal organic frameworks (MOFs), perlite, alumina, glass beads, and mixtures thereof. None of the particles in the particulate bed may be acoustically active, or some or all of them may be acoustically active.
[0136] The porosity of the particulate bed can be adjusted, in part, based on the size distribution of the particles, which may range from 0.1 micrometers to 2000 micrometers, 5 micrometers to 1000 micrometers, 10 micrometers to 500 micrometers, or in some embodiments may be less than, equal to, or greater than 0.1 micrometers, 0.5, 1, 2, 5, 10, 20, 30, 40, 50, 70, 100, 200, 300, 400, 500, 700, 1000, 1500, or 2000 micrometers.
[0137] The aforementioned porous layers can generally be characterized by their specific acoustic impedance, i.e., the ratio of the pressure difference on both sides of the layer in frequency space to the effective velocity approaching the layer surface. In theoretical models based on a rigid film with perforations, for example, the velocity is derived from the air moving in and out of the holes. If the film is flexible, wall motions may contribute to the calculation of the acoustic impedance. The specific acoustic impedance generally varies as a function of frequency and is a complex number, reflecting the fact that pressure and velocity waves can be out of phase with each other.
[0138] As used herein, specific acoustic impedance is measured in MKS Rayls, where 1 MKS Rayl is 1 Pascal-second per meter (Pa s m -1 ) or equivalently 1 newton second per cubic meter (N s m -3 ), or 1 kg s -1 m -2 It is.
[0139] A porous layer can also be characterized by its transfer impedance: for a perforated film, the transfer impedance is the difference between the acoustic impedance on the incident side of the porous layer and the acoustic impedance observed when no perforated film is present, i.e., the acoustic impedance of only the air cavity.
[0140] Flow resistance is the low frequency limit of the transfer impedance. Experimentally, it can be estimated by blowing air at a known low velocity through a porous layer and measuring the associated pressure drop. Flow resistance can be determined by dividing the measured pressure drop by the velocity.
[0141] In embodiments including a perforated film, the flow resistance through the perforated film alone (no non-uniform filler) may be from 50 MKS Rayls to 8000 MKS Rayls, from 100 MKS Rayls to 4000 MKS Rayls, or from 400 MKS Rayls to 3000 MKS Rayls. In some embodiments, the flow resistance through the perforated film is 50 MKS Rayls, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, or 8000 MKS The value of Rayls may be less than, equal to, or greater than these values.
[0142] In embodiments including a nonwoven fibrous layer, the flow resistance through the nonwoven fibrous layer alone (no non-uniform filler) may be from 50 MKS Rayls to 8000 MKS Rayls, from 100 MKS Rayls to 4000 MKS Rayls, or from 400 MKS Rayls to 3000 MKS Rayls. In some embodiments, the flow resistance through the nonwoven fibrous layer is 50 MKS Rayls, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 250, 300, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 1000, 1100, 1200, 1300, 1400, 1500, 1600, 1700, 1800, 1900, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, or 8000 MKS Rayls. The value of Rayls may be less than, equal to, or greater than these values.
[0143] The flow resistance through the overall acoustic article may be from 100 MKS Rayls to 8000 MKS Rayls, from 120 MKS Rayls to 5000 MKS Rayls, or from 150 MKS Rayls to 4000 MKS Rayls. In some embodiments, the flow resistance through the overall acoustic article is less than, equal to, or greater than 10 MKS Rayls, 20, 30, 40, 50, 70, 100, 120, 150, 180, 200, 250, 300, 400, 500, 600, 700, 1000, 1100, 1200, 1500, 1700, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 5500, 6000, 6500, 7000, 7500, or 8000 MKS Rayls.
[0144] Non-uniform packing The acoustic articles described herein can incorporate one or more non-uniform fillers that can provide enhanced acoustic properties. Each of the non-uniform fillers referred to in the above embodiments can have independent and distinct characteristics, as described below.
[0145] Exemplary non-uniform fillers include porous and / or fine non-uniform fillers. Porous and / or fine fillers that can be incorporated into the provided acoustic articles include particles of clay, diatomaceous earth, graphite, glass bubbles, polymeric fillers, non-layered silicates, plant-based fillers, and mixtures thereof. The filler particles can have a variety of shapes, including flake, powder, and fiber shapes. The particles may be primary particles that, in some cases, have agglomerated (i.e., aggregated) into larger particles.
[0146] Clay fillers are widely available and are commonly used in rubber compounding applications to provide reinforcement and improved physical or processing properties. As used herein, clay includes any of a variety of hydrous aluminosilicate minerals found in nature, generally exhibiting a laminated sheet-like microstructure. The main component of clay is kaolin. Kaolin, sometimes called kaolinite, is characterized by alternating layers of alumina and silica. Another useful clay is bentonite, an absorbent aluminum phyllosilicate clay composed primarily of montmorillonite. Other clays may be pure synthetic clays and not obtained from natural sources. One such synthetic clay is LAPONITE, which is composed of silica layers, octahedrally coordinated magnesium, and alkali metal ions.
[0147] In some cases, clay fillers can be converted into other materials by a heating process known as calcination. Calcination temperatures can range from 800°C to 1000°C. At these temperatures, the water of hydration within the clay can be driven off. When sufficiently calcined, the individual mineral platelets can fuse together and the clay becomes relatively inert.
[0148] The heterogeneous filler may also include non-layered silicate materials. Non-layered silicates include alkali silicates, alkaline earth silicates, non-zeolitic aluminosilicates, and geopolymers. Such materials may or may not be zeolitic. An example of a non-zeolitic aluminosilicate material is nepheline, which is an aluminosilicate of sodium and potassium.
[0149] Diatomaceous earth is derived from the fossilized remains of tiny aquatic microorganisms called diatoms. These fossilized remains consist primarily of silica, but also contain small amounts of alumina and iron oxide. In filler form, it is a powder with a polydisperse particle size distribution, generally ranging from 10 micrometers to 200 micrometers. Optionally, diatomaceous earth may be mechanically processed, such as by grinding, to reduce the median particle size. As with the clay minerals described above, diatomaceous earth may be calcined to remove impurities and undesirable volatile components. Chemical processing may also be employed to remove impurities.
[0150] Graphite fillers can be made from expanded graphite, unexpanded graphite, or mixtures thereof. Graphite is a crystalline allotropic form of carbon and can be obtained from natural sources or produced synthetically by heating petroleum coke in a furnace to approximately 3000°C. In its naturally occurring form, graphite is unexpanded. Chemical compounds such as sulfuric acid can be added to produce sp-containing graphite. 2 Unexpanded graphite can be converted to expanded graphite by intercalating between the hybrid carbon sheets. The graphite particles or flakes may then be heated to a temperature above the exfoliation temperature of graphite (typically 150°C to 300°C), causing the graphite layers to separate from each other and expand to several times their original thickness.
[0151] Other forms of porous carbon, not necessarily graphitic, may also be used as the heterogeneous filler. Useful porous carbons include activated carbon fillers and vermiculite carbon fillers, which have unique acoustic properties based on their varying degrees of porosity. Details regarding these materials are described in co-pending International Patent Application PCT / US18 / 56671 (Lee et al.), the disclosure of which on porous carbon fillers is expressly incorporated herein by reference.
[0152] Porous polymer fillers can have a wide range of porosity, making them suitable for acoustic absorption at frequencies below 1000 Hz. These absorption properties have been observed in many polymer compositions, including polypropylene, divinylbenzene-maleic anhydride, styrene-divinylbenzene, and acrylic polymers. Porous polymer fillers include open-cell foams, closed-cell foams, and combinations thereof. An example of a filler made of open-cell polymer foam includes polyolefin foam fillers available under the trade name ACCUREL MP from Evonik Industries AG (Essen, Germany).
[0153] The filler may in some cases aggregate (i.e., clump). Primary filler particles may aggregate with one another due to particle-particle interactions. Such interactions may result from secondary bonding forces or electrostatic forces. In some embodiments, at least a portion of the polymer particles are sintered together under slight pressure and heat to form aggregates. Heat may be provided using any known method, including steam, radio frequency radiation, infrared radiation, or heated air. Particle aggregation may also be achieved by using adhesives or binders.
[0154] The particle aggregates may be of regular or irregular shape. Preferably, the aggregates will remain together in the intended use, and most of the particles will retain the specified dimensions, but are not necessarily "shatter-resistant." In some embodiments, pores within the acoustic article may arise exclusively from interstitial spaces developed between the primary filler particles.
[0155] Plant-based fillers include cellulose-based fillers such as wood flour. Wood flour consists of fine particles of wood and is generally obtained from woodworking operations such as sawing, milling, planing, groove planing, drilling and sanding. Other plant-based fillers include flax, jute, sisal, hemp, wheat and rice straw, rice husk, ash, starch and lignin. Some of these fillers are fibrous in nature, which provides advantages as lightweight reinforcing fillers in composites. Waste shells from cork and nuts contain cellulose and lignin. Plant-based fillers can be very porous.
[0156] Other possible heterogeneous fillers can include non-plant-based biological fillers. These include filler particles derived from waste streams such as chicken feathers or shellfish shells. Fillers may also be derived from fungi, sponges and other biological products outside the plant kingdom.
[0157] The non-uniform fillers can independently have any suitable median particle size. The filler particles can be sized to produce interstitial voids with a desired size distribution when incorporated into a given porous layer. Such voids can represent spaces between filler particles, nonwoven fibers (if present), polymeric or inorganic struts (if present), or combinations thereof. The median particle size of the filler particles is a parameter that can also be used to adjust the permeability (and overall flow resistance) of the acoustic article.
[0158] The heterogeneous filler may have a median particle size of 1 micrometer to 1000 micrometers, 1 micrometer to 100 micrometers, 100 micrometers to 1000 micrometers, 100 micrometers to 800 micrometers, or in some embodiments may have a median particle size less than, equal to, or greater than 1 micrometer, 2, 3, 4, 5, 7, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 70, 80, 90, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900, or 1000 micrometers.
[0159] The heterogeneous fillers disposed within a given porous layer can have any suitable particle size distribution to provide the desired acoustic response. The particle size distribution can be monodisperse or polydisperse. The particle size distribution can be unimodal or multimodal, regardless of how many heterogeneous filler compositions are present in the porous layer. The heterogeneous fillers can have a Dv50 / Dv90 particle size ratio of 0.25 to 1, 0.3 to 0.9, 0.4 to 0.8, or in some embodiments, a Dv50 / Dv90 particle size ratio less than, equal to, or greater than 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.95, or 1.
[0160] Dv50 and Dv90 can be defined by the volume weighted size distribution determined using laser scattering. Given the volume weighted distribution, Dv50 refers to the median particle size, and Dv90 refers to the particle size below which 90% of the filler particles by total volume have a smaller diameter. Such distribution can also be adjusted by using test sieves to exclude particles of a certain diameter.
[0161] The non-uniform packing material can independently have any suitable specific surface area. Due to the nature of the porosity, the non-uniform packing material can exhibit a high surface area. Having a high surface area can reflect a high degree of complexity and tortuosity of the pore structure, which leads to a large internal reflection and energy transfer to the solid structure through frictional losses. Advantageously, this can be expressed as the absorption of airborne noise.
[0162] The specific surface area of the non-uniform packing is 0.1 m 2 / g~100m 2 / g, 1m 2 / g~100m 2 / g, 100m 2 / g~800m 2 / g, 0.1m 2 / g~800m 2 / g, or in some embodiments, 0.1 m 2 / g, 0.2, 0.5, 0.7, 1, 2, 5, 10, 20, 50, 100, 120, 150, 200, 250, 300, 350, 400, 450, 500, 6000, 700, 800, 900, 1000, 1500, 2000, 2500, 3000, 3500, 4000, 4500, 5000, 6000, 7000, 8000, 9000, or 10,000m 2 The value of / g may be less than, equal to, or greater than these values.
[0163] Surface area can be measured based on the adsorption of either nitrogen or krypton gas onto the surface of a given material at liquid nitrogen temperature. These measurements can be performed using a device known as a gas adsorption analyzer. In this measurement, an isotherm (volume of gas absorbed per unit mass at standard temperature and pressure versus relative pressure) can be generated by dosing the sample with gas. The specific surface area can then be calculated by applying a modified form of the Langmuir equation, known as the Brunauer-Emmett-Teller (BET) equation, to the isotherm. This value is known as the BET specific surface area. In some embodiments, the specific surface area referred to herein is the BET specific surface area.
[0164] In some embodiments, the heterogeneous filler is characterized by extremely fine pores. The heterogeneous filler may have an average pore size of 0.4 nanometers to 50 micrometers, 1 nanometer to 40 micrometers, 2.5 nanometers to 30 micrometers, or in some embodiments, may have an average pore size less than, equal to, or greater than 0.1 nanometers, 0.2, 0.3, 0.4, 0.5, 1, 1.2, 1.5, 1.7, 2, 3, 4, 5, 7, 10, 15, 20, 25, 30, 40, 50, 70, 100, 150, 200, 250, 300, 350, 400, 450, 500, 600, 700, 800, 900 nanometers, 1 micrometer, 2, 3, 4, 5, 7, 10, 15, 20, 25, 30, 35, 40, 45, or 50 micrometers.
[0165] Heterogeneous filler particles may have pore sizes much smaller than conventional fillers used in acoustic applications. For example, the smallest pores of certain polymers with intrinsic microporosity may be less than 2 nm in diameter. In contrast, calcined diatomite generally contains pores from hundreds of nanometers to tens of micrometers. In general, heterogeneous fillers may have smallest pore sizes of up to 10,000 nm, up to 5,000 nm, up to 2,000 nm, up to 1,000 nm, up to 500 nm, up to 400 nm, up to 300 nm, up to 200 nm, up to 100, up to 50, up to 20, up to 10, up to 5, up to 2, and up to 1 nm.
[0166] The uneven filling is 0.01 cm 3 / g~5cm 3 In some embodiments, the total pore volume is 0.01 cm 3 / g, 0.02, 0.05, 0.07, 0.1, 0.2, 0.3, 0.4, 0.5, 0.7, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.5, 3, 3.5, 4, 4.5, or 5 cm 3 The values of / g may be less than, equal to, or greater than these values.
[0167] The bonding of the heterogeneous filler to the porous layer can be promoted by the modification of the particle surface via silane or other metal or metalloid complexes. Depending on the functional groups present, either intermolecular or intramolecular bonding to the layer can be achieved. The polymer heterogeneous filler (or aggregates containing the polymer binder) can be modified by a variety of routes, including various forms of grafting, solvent treatment, and electron beam irradiation. These modifications can also promote the bonding of the particles to the porous layer.
[0168] Manufacturing method The provided acoustic articles can be assembled using any of a number of suitable manufacturing methods.
[0169] In embodiments where the porous layer is a nonwoven fibrous web, the nonuniform filler can be incorporated into the construct fibers either during or after the direct formation of the fibers. When the nonwoven fibrous web is produced using a meltblowing process, for example, the nonuniform filler can be blown onto a rotating collector drum while being conveyed and comixed with a stream of molten polymer. The nonuniform filler can be entrained in a flow of heated air that converges with the hot air used to attenuate the meltblown fibers. An exemplary process is described in U.S. Pat. No. 3,971,373 (Braun). Similarly, particles of nonuniform filler can be conveyed during an airlaid process, such as using the process to produce a porous layer made from recycled textile fibers (i.e., shoddy).
[0170] The non-uniform filler can also be added after the non-woven fibrous layer is produced. For example, the non-uniform filler can be uniformly dispersed in a liquid medium such as water due to the porosity of the non-woven fibrous layer, and then the particulate-loaded medium can be roll-coated or slurry-coated onto the non-woven porous layer to allow the non-uniform filler to penetrate into the interstitial spaces. Instead of using a liquid medium, the non-uniform filler can be entrained in a gaseous flow such as an air flow, and then the flow can be guided to the non-woven layer to load it.
[0171] Alternatively, the non-uniform filler can be captured in the porous layer by agitation. In one embodiment of this method, a non-woven fibrous layer is placed on a flat surface and a cylindrical conduit is placed on top to define the coating area. Particles of the non-uniform filler can then be poured into the conduit and the assembly can be agitated until the particles are sufficiently transferred through the open pores into the non-woven structure. A similar method can be used for a porous layer composed of open-cell foam.
[0172] The construction of the multi-layer acoustic article and its attachment to the substrate can include one or more lamination steps. Lamination can be achieved using adhesive bonding. Preferably, any adhesive layer used does not prevent sound transmission to the absorbent layer. Alternatively or in combination, physical entanglement of the fibers can be used to improve interlayer adhesion. Mechanical bonding, for example using fasteners, is also possible.
[0173] Acoustic articles may also be edge sealed to prevent the escape of particles. Such containment may be achieved by densifying the edges, filling the edges with resin, quilting the acoustic article, or completely encasing the acoustic article in a sleeve to prevent migration or escape of particles. Edge sealing may be desirable to improve product life, durability, and ease of handling and installation. Edge sealing may also be performed for aesthetic reasons.
[0174] In yet another embodiment, the nonwoven fibrous layer may be sprayed sequentially with the adhesive and then with the filler particles. In some examples, the adhesive may be provided in the form of hot melt fibers.
[0175] Although not intended to be limiting, various exemplary embodiments are listed below. 1. An acoustic article, comprising: a porous layer; and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 1 micrometer to 100 micrometers and a median particle size of 0.1 micrometer to 10 micrometers. 2 / g~100m 2 / g and a non-uniform filler having a specific surface area of 100 MKS Rayls to 8000 MKS Rayls, wherein the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls. 2. An acoustic article, comprising: a porous layer; and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 100 micrometers to 800 micrometers and a median particle size of 100 micrometers to 800 micrometers. 2 / g~800m 2 / g and a non-uniform filler having a specific surface area of 100 MKS Rayls to 8000 MKS Rayls, wherein the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls. 3. An acoustic article comprising a porous layer and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 100 micrometers to 1000 micrometers and a median particle size of 1 m 2 / g~100m 2 / g and a non-uniform filler having a specific surface area of 100 MKS Rayls to 8000 MKS Rayls, wherein the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls. 4. The acoustic article of any one of embodiments 1-3, wherein the non-uniform filler comprises clay, diatomaceous earth, graphite, glass bubbles, polymeric fillers, non-layered silicates, plant-based fillers, or combinations thereof. 5. The acoustic article of embodiment 4, wherein the heterogeneous filler comprises a non-layered silicate, the non-layered silicate being an alkali silicate, an alkaline earth silicate, a non-zeolitic aluminosilicate, or a geopolymer. 6. The acoustic article of embodiment 4, wherein the non-uniform filler comprises graphite, and the graphite is non-expanded graphite. 7. The acoustic article of embodiment 4, wherein the heterogeneous filler comprises a porous polymeric filler, the porous polymeric filler comprising a polyolefin foam, polyvinylpyrrolidone, divinylbenzene, divinylbenzene-maleic anhydride, styrene-divinylbenzene, or a polyacrylate. 8. The acoustic article of embodiment 4, wherein the heterogeneous filler comprises a plant-based filler, and the plant-based filler comprises wood flour. 9. An acoustic article, comprising: a porous layer; and a non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 m. 2 / g~800m 2 / g and a non-uniform filler comprising diatomaceous earth, plant-based filler, unexpanded graphite, polyolefin foam, or a combination thereof, wherein the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls. 10. The non-uniform filler includes diatomaceous earth, the diatomaceous earth having a median particle size of 5 micrometers to 40 micrometers and a median particle size of 1 m 2 / g~50m 2 10. The acoustic article of embodiment 9, having a specific surface area of 100 / g. 11. Uneven filling material, 1m 2 / g~40m 2 11. The acoustic article of embodiment 10, having a specific surface area of 1.0 nm to 1.5 nm / g. 12. Uneven filling material, 20m 2 / g~40m 2 12. The acoustic article of embodiment 11, having a specific surface area of 1.0 nm to 1.0 nm / g. 13. The non-uniform filler includes a plant-based filler, and the plant-based filler has a median particle size of 10 micrometers to 1000 micrometers and a median particle size of 0.1 m 2 / g~200m 2 10. The acoustic article of embodiment 9, wherein the wood flour has a specific surface area of 100 / g. 14. Wood flour has a median particle size of 50 micrometers to 800 micrometers and a median particle size of 0.1 m 2 / g~50m 2 14. The acoustic article of embodiment 13, having a specific surface area of 0.1 mm to 0.2 mm. 15. Wood flour has a median particle size of 50 to 400 micrometers and a median particle size of 0.1 m 2 / g~10m 2 15. The acoustic article of embodiment 14, having a specific surface area of 1.0 nm to 1.5 nm / g. 16. The non-uniform filler comprises non-expanded graphite, the non-expanded graphite having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 micrometer to 1000 micrometers. 2 / g~500m 2 10. The acoustic article of embodiment 9, having a specific surface area of 100 / g. 17. Non-expanded graphite has a median particle size of 5 micrometers to 800 micrometers and a median particle size of 1 m 2 / g~300m 2 17. The acoustic article of embodiment 16, having a specific surface area of 0.1 mm to 1.0 mm / g. 18. Non-expanded graphite has a median particle size of 100 micrometers to 1000 micrometers and a median particle size of 1 m 2 / g~100m 2 18. The acoustic article of embodiment 17, having a specific surface area of 0.1 mm to 0.5 mm. 19. The non-uniform filler comprises a polyolefin foam, the polyolefin foam having a median particle size of 100 micrometers to 1000 micrometers and a median particle size of 1 m 2 / g~100m 2 10. The acoustic article of embodiment 9, having a specific surface area of 100 / g. 20. Polyolefin foam has a median particle size of 100 micrometers to 500 micrometers and a particle size of 1 m 2 / g~50m 2 20. The acoustic article of embodiment 19, having a specific surface area of 0.1 mm to 1.0 mm / g. 21. Polyolefin foam has a median particle size of 100 to 200 micrometers and a median particle size of 5 m 2 / g~35m 2 21. The acoustic article of embodiment 20, having a specific surface area of 100 / g. 22. The acoustic article of any one of embodiments 1-21, wherein the non-uniform filler is dispersed throughout the thickness of the porous layer. 23. The acoustic article of any one of embodiments 1-22, wherein the non-uniform filler has an open-cell structure. 24. The acoustic article of any one of embodiments 1-23, wherein the non-uniform filler is agglomerated. 25. The acoustic article of any one of embodiments 1-24, wherein the non-uniform filler has a Dv50 / Dv90 particle size ratio of 0.25 to 1. 26. The acoustic article of embodiment 25, wherein the non-uniform filler has a Dv50 / Dv90 particle size ratio of 0.3 to 0.9. 27. The acoustic article of embodiment 26, wherein the non-uniform filler has a Dv50 / Dv90 particle size ratio of 0.4 to 0.8. 28. The acoustic article of any one of embodiments 1-27, wherein the porous layer comprises a nonwoven fibrous layer having a plurality of fibers. 29. The acoustic article of embodiment 28, wherein the plurality of fibers have a median fiber diameter of from 0.1 micrometers to 2000 micrometers. 30. The acoustic article of embodiment 29, wherein the plurality of fibers have a median fiber diameter of from 5 micrometers to 1000 micrometers. 31. The acoustic article of embodiment 30, wherein the plurality of fibers have a median fiber diameter of from 10 micrometers to 500 micrometers. 32. The acoustic article of any one of embodiments 28-31, wherein the plurality of fibers comprises a polymer selected from polyolefin, polypropylene, polyethylene, polyester, polyethylene terephthalate, polybutylene terephthalate, polyamide, nylon 6,6, polyurethane, polybutene, polylactic acid, polyphenylene sulfide, polysulfone, liquid crystal polymer, polyethylene-co-vinyl acetate, polyacrylonitrile, cyclic polyolefin, or copolymers or blends thereof. 33. The acoustic article of any one of embodiments 28-32, wherein the plurality of fibers comprises a thermoplastic semicrystalline polymer. 34. The acoustic article of any one of embodiments 28-33, wherein the plurality of fibers comprises meltblown fibers. 35. The acoustic article of any one of embodiments 28-34, wherein the plurality of fibers comprises recycled textile fibers. 36. The acoustic article of any one of embodiments 28-35, wherein the plurality of fibers comprises glass fibers or ceramic fibers. 37. The acoustic article of any one of embodiments 28-36, wherein the plurality of fibers has an average fiber-to-fiber spacing of between 0 micrometers and 1000 micrometers. 38. The acoustic article of embodiment 37, wherein the plurality of fibers have an average fiber-to-fiber spacing of 10 micrometers to 500 micrometers. 39. The acoustic article of embodiment 38, wherein the plurality of fibers have an average fiber-to-fiber spacing of 20 micrometers to 300 micrometers. 40. The acoustic article of any one of embodiments 1-27, wherein the porous layer comprises an open-cell polymer foam. 41. The acoustic article of any one of embodiments 1-27, wherein the porous layer comprises a perforated film. 42. The acoustic article of embodiment 41, wherein the perforated film has a thickness of from 1 micrometer to 10 centimeters. 43. The acoustic article of embodiment 42, wherein the perforated film has a thickness of from 30 micrometers to 1 centimeter. 44. The acoustic article of embodiment 43, wherein the perforated film has a thickness of from 50 micrometers to 5000 micrometers. 45. The acoustic article of any one of embodiments 41-44, wherein the perforations have an average minimum diameter of 10 micrometers to 5000 micrometers. 46. The acoustic article of embodiment 45, wherein the perforations have an average minimum diameter of 10 micrometers to 3000 micrometers. 47. The acoustic article of embodiment 46, wherein the perforations have an average minimum diameter of 20 micrometers to 1500 micrometers. 48. The acoustic article of any one of embodiments 41-47, wherein the perforated film comprises a material having a flexural modulus of 0.2 GPa to 10 GPa. 49. The acoustic article of embodiment 48, wherein the perforated film comprises a material having a flexural modulus of 0.2 GPa to 7 GPa. 50. The acoustic article of embodiment 49, wherein the perforated film comprises a material having a flexural modulus of 0.2 GPa to 4 GPa. 51. The acoustic article of any one of the preceding embodiments, wherein the non-uniform filler has an average interparticle spacing of from 20 micrometers to 4000 micrometers. 52. The acoustic article of embodiment 51, wherein the non-uniform filler has an average interparticle spacing of 50 micrometers to 2000 micrometers. 53. The acoustic article of embodiment 52, wherein the non-uniform filler has an average interparticle spacing of 100 micrometers to 1000 micrometers. 54. The acoustic article of any one of embodiments 1-53, wherein the porous layer filled with non-uniform filler has a solidity of 5 percent to 40 percent. 55. The acoustic article of embodiment 54, wherein the porous layer filled with non-uniform filler has a solidity of 8 percent to 35 percent. 56. The acoustic article of embodiment 55, wherein the porous layer filled with the non-uniform filler has a solidity of 10 percent to 30 percent. 57. The acoustic article of any one of the preceding embodiments, further comprising a plurality of Helmholtz resonators in contact with the porous layer. 58. A method of making an acoustic article, comprising: directly forming a nonwoven fibrous web; and delivering a nonuniform filler to the nonwoven fibrous web as the nonwoven fibrous web is being directly formed, the nonuniform filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 m. 2 / g~800m 2 and delivering a filler material comprising diatomaceous earth, plant-based filler, unexpanded graphite, polyolefin foam, or combinations thereof, having a specific surface area of 100 MKS Rayls to 8000 MKS Rayls. 59. The method of embodiment 58, wherein the nonwoven fibrous web is directly formed using a meltblowing or airlaid process. 60. The method of embodiment 58 or 59, wherein the nonwoven fibrous web comprises a nonwoven fibrous web comprising a plurality of fibers, and the nonuniform filler is at least partially entrapped within the plurality of fibers. 61. A method of using an acoustic article according to any one of embodiments 1 to 57, comprising placing the acoustic article in proximity to a surface to dampen vibrations of the surface. 62. A method of using an acoustic article according to any one of embodiments 1 to 57, comprising placing the acoustic article in proximity to an air cavity to absorb sound energy transmitted through the air cavity. 63. A method of using the acoustic article of embodiment 62, wherein absorption of sound energy occurs with essentially zero net flow of fluid through the acoustic article. EXAMPLES
[0176] Objects and advantages of the present disclosure are further illustrated by the following non-limiting examples, but the specific materials and amounts thereof recited in these examples, as well as other conditions and details, should not be construed as unduly limiting this disclosure.
[0177] Unless otherwise noted, all parts, percentages, ratios, etc. in the examples and elsewhere in the specification are by weight.
[0178] [Table 1]
[0179] Test Method Laser scattering particle size analysis The size distribution of the unsized materials was measured by laser scattering using a Horiba LA-950V2 (Horiba, Ltd., Kyoto, Japan). Dispersions of a given material were prepared at solids contents of around 0.3% to 0.5% by weight for various materials, either in water or in methyl ethyl ketone (MEK). These dispersions were added to the measurement cell containing the corresponding solvent used for the dispersion. This addition was made until the transmittance was between the recommended levels for the instrument. A standard algorithm in the supplied software was used to determine the distribution based on the scattering measurements. In these calculations, liquid refractive indices of 1.33 and 1.3791 were used for water and methyl ethyl ketone (MEK). The refractive indices used for the solids are listed in Table 2. The lower and upper particle sizes correspond to Dv10 and Dv90.
[0180] Gas adsorption Materials were analyzed using a Micromeritics ASAP 2020 (Micromeritics Instrument Corp., Norcross, GA) gas sorption analyzer. Specimens were loaded into bulbous Micromeritics 1.27 cm (1 / 2 inch) diameter sample tubes and outgassed at 0.4 Pa to 0.9 Pa (3 microns to 7 microns of mercury). The temperature and time of outgassing are shown in Table 2. After nitrogen sorption analysis, free space was determined using helium at both ambient temperature and 77 K. Isotherms were measured using nitrogen gas at 77 K over the pressure range of 0.025 P / Po to 0.3 P / Po, and multipoint Brunauer-Emmett-Teller (BET) specific surface area calculations were performed. The exact points used in this calculation were varied from sample to sample to obtain positive C values.
[0181] Bulk density Bulk density was measured according to ASTM D7481-18, Method A (loose bulk density).
[0182] Skeletal Density - Pycnometry Skeletal density of the materials was obtained using a Micromeritics ACCUPYC II 1340 TEC pycnometer (Micromeritics, Norcross, GA, USA). Helium gas was used. Prior to taking measurements, the instrument was calibrated for the volume to be measured using a metal sphere of specified traceable volume. A 3.5cc cup was used for the measurements, and measurements were taken at ambient temperature.
[0183] Normal Incidence Sound Absorption Normal incidence acoustic absorption was tested according to ASTM E1050-12 "Standard Test Method for Impedance and Absorption of Acoustical Materials Using a Tube, Two Microphones and a Digital Frequency Analysis System". An "IMPEDANCE TUBE KIT (50HZ-6.4KHZ) TYPE 4206" available from Bruel & Kjaer (Denmark) was used. The impedance tube was 63 millimeters (mm) in diameter and oriented vertically, and the microphones were above the sample chamber. Normal incidence absorption coefficients were reported in terms of 1 / 3 octave band frequencies using the abbreviation "α". Two samples were tested for each material, and the average normal incidence absorption coefficient was recorded.
[0184] Air Flow Resistance (AFR) Test 1 Airflow resistance was measured on 13.5 cm (5.25 in) samples in accordance with ASTM C-522-03 (reapproved 2009), "Standard Test Method for Airflow Resistance of Acoustical Materials." The equipment used was a "SIGMA Static Airflow Resistance Meter" running "SIGMA-X" software (both from Mecanum, Sherbrooke, Canada).
[0185] Airflow Resistance (AFR) Test 2 A TSI.TM. Model 8130 high speed automated filter tester (available from TSI Inc.) was operated with particle generation and measurement turned off. The flow rate was adjusted to 11.1 liters per minute (LPM) and two annular panels covered the measurement area to a 41.3 mm (1.625 inch) diameter circle providing equivalent results to a 114.3 mm (4.5 inch) diameter sample measured at 85 LPM. The sample was placed in the lower circular plenum opening and the AFT was engaged. An MKS pressure transducer (available from MKS Instruments) within the device measured the pressure drop in mm H2O. Measurements were converted to MKS Rayls using the linear relationship AFR [MKS Rayls] = 71.035 x pressure drop (mm H2O measured at 85 LPM).
[0186] Preparation of particles Particle agglomeration Particle agglomeration was carried out using the following materials: CLOISITE Na+, Laponite RD, iM30K, CLARCEL 78, TC307 and A4958. RHOPLEX VSR-50 was used as the binder. The weight percentages of acoustically active microparticles, binders and deionized (DI) water used to produce the agglomerated particles are listed in Table 2.
[0187] [Table 2]
[0188] The materials were mixed in a KitchenAid KFC3511GA food processor (Whirlpool Corporation, Benton Charter Township, MI). During the addition of the binder and water suspension, the materials were periodically broken up using a spatula to ensure even distribution of the binder. After mixing, the aggregates were heated overnight at 50° C. for drying. Once dry, the aggregates were sized using two wire mesh screens (Retsch GmbH, Haan, Germany), one with 1 millimeter (mm) openings and the second with 106 micrometer openings. Any aggregate material that passed through the 1 millimeter screen and was rejected by the 106 micrometer screen was used for further acoustic testing.
[0189] Firing CLARCEL 78 was loaded into a porcelain crucible and heated at 600 °C for 12 h under static air in a Lindberg / Blue M Heavy Duty Box Furnace (ThermoFisher Scientific, Waltham, MA).
[0190] Milling The DVB-MA porous copolymer material was milled using a rotary mill with a 2.0 mm sieve screen manufactured by IKA (Wilmington, NC).The milled material was then sieved using USA Standard Test No. 30, 40 and 60 wire mesh sieves (ASTM E-11 standard; Hogentogler and Co., Inc. Columbia, MD) and a Meinzer II Sieve Shaker (CSC Scientific Company, Inc., Fairfax, Va) for 15 minutes to isolate all materials with sizes less than 30 mesh (DVB-MA-1), 30×40 mesh (DVB-MA-2), 40×60 mesh (DVB-MA-3) and greater than 60 mesh (DVB-MA-4), and then the separated materials were collected.
[0191] Geopolymer Assembly The parent sodium geopolymer samples (geopolymer) were prepared by dissolving potassium hydroxide (85% in water, Millipore Sigma, Burlington, MA) in deionized water, followed by the addition of a proportional amount of sodium silicate ("STAR", PQ Crop, Malvern, PA) along with metakaolin powder (Metamax, BASF Ludwigshafen, Germany). The mixture was vigorously stirred for about 10 minutes and then poured into a plastic container. The parent geopolymer was formulated to the following molar ratios: Si / Al=2.8, Na / Al=3, HO / Al=10. Polycondensation was carried out in a closed vessel at 60°C for 24 hours in a laboratory oven. After aging for more than one week, the geopolymer samples were milled in a zirconia vessel containing zirconia milling media using a SPEX 8000 Mixer-mill (SPEX Sample Prep, Metuchen, NJ). The milled geopolymer was sized using two wire mesh screens, one with 1 millimeter (mm) openings and the second with 106 micrometer openings (Retsch GmbH, Haan, Germany). Any material that passed through the 1 millimeter screen and was rejected by the 106 micrometer screen was used for further acoustic testing.
[0192] Particle / agglomerate characterization The samples (aggregated and non-aggregated) were subjected to laser scattering particle size analysis, gas sorption, surface area, bulk density and skeletal density tests and characterized as presented in Table 3. The particles (aggregated or non-aggregated) dispersed in MEK for laser scattering particle size analysis are identified in Table 3. * indicates that the data was obtained from the manufacturer, ** refers to the geometric calculation being converted into a measurement by assuming a d10 spherical diameter of the particle.
[0193] [Table 3]
[0194] The particles (agglomerated and unagglomerated) were subjected to normal incidence acoustic absorption testing and the results are presented in Table 4. Pouring the sample particles into a vertically mounted tube produced a particle bed 20 mm thick, except for the CLARCEL 78-calcined agglomerates, CLOISITE Na+-agglomerates and geopolymer particles, which produced particle beds 15 mm, 15 mm and 10 mm thick. The designation "n / a" indicates that no peak was observed at the specified frequency.
[0195] [Table 4]
[0196] Examples 1 to 19 (EX1 to EX19) and Comparative Example 1 (CE1) Nonwoven meltblown webs were prepared by a process similar to that described in Wente, Van A., "Superfine Thermoplastic Fibers," Industrial Engineering Chemistry, Vol. 48, pp. 1342 et seq. (1956), and Naval Research Laboratories Report No. 4364, by Wente, Van A. Boone, CD, and Fluharty, EL, entitled "Manufacture of Superfine Organic Fibers," published May 25, 1954, except that a drill die was used to produce the fibers.
[0197] MF650Y polypropylene resin was extruded through a die into a high velocity heated air stream, which stretched and attenuated the polypropylene blown microfibers, after which the resin was solidified and collected. Particles were fed into the polypropylene blown microfiber stream according to the method of U.S. Pat. No. 3,971,373 (Braun). The blend of polypropylene blown microfibers and particles was randomly collected on a nylon belt to obtain a particle-filled polypropylene BMF web layer. The web was then removed from the nylon belt to provide the final article. The configuration of the manufactured samples is presented in Table 5. The thickness of the samples was measured at an applied pressure of 150 Pa using a thickness test gauge with a tester foot measuring 5 cm by 12.5 cm. Airflow resistance (AFR) test 1 was performed on the samples. The solidity was calculated based on Equation 1. The results are listed in Table 5.
number
[0198] [Table 5]
[0199] The samples were subjected to normal incidence sound absorption testing and the results are presented in Table 6. For sound absorption, sample disks were punched out using a 64 mm diameter punch and mounted between two circular open mesh metal screens (63 mm and 68 mm) set 5 mm apart from each other above a 20 mm air space. The air space was defined by two 10 mm spacer rings (inner diameter 61 mm), with the 63 mm metal screen resting on the upper spacer ring, which was 5 mm below the lip of the sample chamber volume, while the 68 mm metal screen rested on the lip of the impedance tube sample volume. The spacer and screen (S&S) contributions to α are also provided in Table 6.
[0200] [Table 6]
[0201] Examples 20 to 21 (EX20 to EX21) Two thicker MP1004 filled samples were prepared according to the methods described in Examples 1 to 20. The composition, percent solidity and results of Air Flow Resistance (AFR) Test 2 for the samples produced are presented in Table 7.
[0202] [Table 7]
[0203] The samples were subjected to normal incidence sound absorption testing and the results are presented in Table 8. For sound absorption, sample disks were punched out using a 64 mm diameter punch and placed directly in the sample chamber set at a gap height of 15 mm.
[0204] [Table 8]
[0205] Examples 22 to 28 (EX22 to EX28) and Comparative Example 2 (CE2) Examples were prepared from webs produced by meltblowing 3860X resin heated to 230°C and extruded at a rate of 0.30 grams per minute per hole into sonic heated air at 320°C with an air flow of 9.26 cubic meters per minute. The collector consisted of a 76 cm diameter drum and a 25 cm diameter drum spaced 1 cm apart, each drum having a surface speed of 254 cm / min. The drums operated with an in-running nip to form a fabric with 80% open area and 3 mm staggered holes punched into them.
[0206] The die exited the gap between the drums was 43 cm and the fibers were aligned in the center of the gap. 2A 106 gram web was produced per square inch. The web had one side with pores less than 40 micrometers in diameter and the other side, which corresponded to the small drum, had pores greater than 300 micrometers in diameter.
[0207] The web was rolled onto a flat surface and a sample disk of the BMF nonwoven was punched out using a 64 mm diameter punch, placing approximately 0.2-0.3 grams of particles on the BMF surface. The sample was then loaded onto a shaking table for 1 min and the final mass was taken taking into account the shaken off particles. The sample configuration is presented in Table 9. After performing the acoustic measurements, the Airflow Resistance (AFR) test 2 was performed and the results are presented in Table 9. Since some particles moved during the pressure drop measurement, the measurements are considered lower due to the constraints on the possible pressure drop.
[0208] [Table 9]
[0209] The samples were subjected to normal incidence sound absorption testing and the results are presented in Table 10, except that only one sample was tested.
[0210] [Table 10]
[0211] Examples 29 to 34 (EX29 to EX34) and Comparative Examples 3 to 12 (CE3 to CE12) The shoddy material (Janesville Acoustics, Southfield, MI) was physically separated into discreet fibers using a Rando Reclaim Shredder Model RRS 36 available from Rando Machine Corporation Macedon, NY, with a feed roll setting of 152.4 mm per minute (0.5 ft per minute) and the main cylinder set at 500 RPM. The spread fibers contained some clumps that remained unspread and were manually removed. 400 grams of spread fibers were combined with 100 grams of 2d Melty PET / PET Bi-component (length: 38 mm, 2.0 denier) and 100 grams of sample particulate manufactured by Huvis, Seoul, Korea. Webs were produced from these mixtures on a scrim (obtained as "10.5# CARRIER TISSUE, GRADE 3533" from Little Rapids Corporation, Milwaukee, WI) following the procedure outlined in Example 1 of U.S. Patent No. 9,580,848 (Henderson et al.). Sample constructions and results of Airflow Resistance (AFR) Test 2 are presented in Table 11.
[0212] [Table 11]
[0213] For CE3, CE4, CE7, and CE11, the scrim was too firmly attached to the sample to be removed (DNR: did not remove), and therefore Air Flow Resistance (AFR) Test 2 could not be performed (DNT: did not test).
[0214] The samples were subjected to normal incidence sound absorption testing. For sound absorption, sample disks were punched out using a 64 mm diameter punch and placed directly in the sample chamber set at a gap height of 7 mm.
[0215] For one format of normal incidence sound absorption testing, sample disks were punched out using a 64 mm diameter punch and placed directly into the sample chamber set at a gap height of 7 mm. Measurements were taken both 1) with the scrim side up and 2) with the scrim removed (for AC 32x60 and XG-3) or with the scrim side down (for the control, the scrim was strongly adhered). The results are presented in Table 12.
[0216] [Table 12]
[0217] In an alternative configuration for normal incidence sound absorption testing, a 68 mm diameter punch was used to punch out sample disks and place them on a 68 mm wire mesh circle above a 20 mm gap. Prior to measurement, the scrim was removed from the AC 32x60 and XG-3 samples, while the control (particles=none) sample was tested scrim side down. Results are recorded in Table 13.
[0218] [Table 13]
[0219] In yet another configuration of the normal incidence sound absorption test, samples with particles were tested in two and three layer stacks directly in the sample chamber. The gap heights tested were 18mm for CE9, 24mm for CE10, 15mm for EX32 and 20mm for EX33. The test results are recorded in Table 14.
[0220] [Table 14]
[0221] The samples were also tested for sound absorption according to SAE J2883 "Laboratory Measurement of Random Incidence Sound Absorption Tests Using a Small Reverberation Room". The equipment used was an "ALPHA CABIN" from Autoneum (Winterthur, Switzerland). The tests were performed at a 1.20m 2 The materials were used in a 10 mm frame at 22° C. and 55% humidity. The test results are presented in Table 15. For CE11, the samples were tested with the scrim facing up. For CE12 and EX34, the scrim was positioned facing up and then the scrim was removed before testing.
[0222] [Table 15]
[0223] Examples 35 to 56 (EX35 to EX56) and Comparative Examples 13 to 17 (CE13 to CE19) Discs were cut from the CE3 shoddy nonwoven web using a 64 mm punch. These discs were weighed and then loaded with particles by manually imprinting the particles onto the non-scrim surface of the nonwoven disc. Once the surface was completely filled with particles, the disc was agitated to remove excess and re-weighed. For normal incidence acoustic absorption, samples were loaded into test tubes with the particle-filled surface facing up. A depth of 7 mm was used for the sample chamber, which was completely occupied by a given disc. The results are presented in Table 16. After the acoustic measurements, the results of Airflow Resistance (AFR) Test 1 were recorded and are presented in Table 16.
[0224] [Table 16]
[0225] The sample disk was placed directly into the sample chamber set at a gap height of 7 mm and the sample was subjected to normal incidence sound absorption testing. The results are presented in Table 17.
[0226] [Table 17]
[0227] Examples 57 to 58 (EX57 to EX58) and Comparative Example 20 (CE20) A 2.54 cm (1 inch) thick polyester acoustical absorbing foam (obtained under the trade designation "J81 Tufcote" from AEARO Technologies, Indianapolis, IN) was used as the base substrate. Sample disks were punched out using a 64 mm diameter punch and a razor was used to remove the skin layers from both sides of the disk. For each disk, 0.3 g of particles were hand-spread over the entire surface. The sample configurations and results of Airflow Resistance (AFR) Test 2 are presented in Table 18.
[0228] [Table 18]
[0229] The sample disk was placed directly into the sample chamber set at a gap height of 20 mm and the sample was subjected to normal incidence sound absorption testing. The results are presented in Table 19. For each particle, only one sample was tested.
[0230] [Table 19]
[0231] Example 59 (EX59) and Comparative Examples 21 to 22 (CE21 to CE22) Fiberglass material (obtained from the hood liner of a 2018 Honda Odyssey Elite) was used as the base substrate. The scrim was removed from both sides and sample disks were punched out using a 64 mm diameter punch. For each disk, 0.3 g of particles was hand-spread across the entire surface. The sample configurations and results of Airflow Resistance (AFR) Test 2 are presented in Table 20. Only one sample of each particle was tested.
[0232] [Table 20]
[0233] The sample disc was placed directly into the sample chamber set at a gap height of 20 mm and the sample was subjected to normal incidence sound absorption testing. The results are presented in Table 21.
[0234] [Table 21]
[0235] Examples 60 to 93 (EX60 to EX93) and Comparative Examples 23 to 26 (CE23 to CE26) Microperforated films were prepared as described in US Patent No. 6,617,002 (Wood). For MF-1, film grade polypropylene resin PP-1 was used to extrude polypropylene film (thickness 1.5 mm) and 3 wt% black masterbatch (PP3019, obtained from RTP Company, Winona, MN, USA) was added. For MF-2, film grade polypropylene resin PP-1 was used to extrude polypropylene film (thickness 0.52 mm) and red masterbatch (199X141358SS-57495, obtained from RTP Company) was added. The film was embossed and heat treated to produce apertures at the embossed portions. The geometry of the apertures was obtained as described in co-pending international patent application PCT / US18 / 56671 (Lee et al.), filed October 19, 2018. The aperture dimensions, recorded as average values in micrometers (μm), are listed in Table 22.
[0236] [Table 22]
[0237] Sample disks were punched using a 68 mm diameter punch. For each disk, an attempt was made to fill the openings and the particles were hand spread on the side with the larger openings. The sample configurations and results of Air Flow Resistance (AFR) Test 1 for some of the samples are presented in Table 23. (DNT = not tested).
[0238] [Table 23]
[0239] The sample disks were placed directly on top of a 68 mm metal screen resting on the lip of the sample chamber, set at a gap height of 20 mm, and the samples were subjected to normal incidence acoustic absorption testing. Where a single composite configuration is reported, the composite was measured once, the particles shaken off, and then the same particles were introduced to the same micro-perforated film for a second acoustic measurement. Where two composite configurations are reported, two sets of particles and films were measured. Results were not averaged. Results for MF-1 are presented in Table 24 and results for MF-2 are presented in Table 25.
[0240] [Table 24]
[0241] [Table 25]
[0242] All references, patent documents and patent applications cited in the above patent application are incorporated herein by reference in their entirety for consistency. In the event of any inconsistency or discrepancy between any of the incorporated references and this application, the information in the above description shall prevail. The above description is intended to enable a person skilled in the art to practice the disclosure as set forth in the claims, and should not be construed as limiting the scope of the disclosure, which is defined by the claims and all equivalents thereof.
Claims
1. 1. An acoustic article comprising: A porous layer; A non-uniform filler received in the porous layer, the non-uniform filler having a median particle size of 1 micrometer to 100 micrometers and a median particle size of 0.1 micrometer to 10 micrometers. 2 / g to 100m 2 and a non-uniform filler having a specific surface area of 100 / g; the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls; the non-uniform filler being agglomerated.
2. 1. An acoustic article comprising: A porous layer; A non-uniform filler received in the porous layer, the filler having a median particle size of 100 micrometers to 800 micrometers and a median particle size of 100 micrometers to 800 micrometers. 2 / g~800m 2 and a non-uniform filler having a specific surface area of 100 / g; the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls; the non-uniform filler being agglomerated.
3. 1. An acoustic article comprising: A porous layer; A non-uniform filler received in the porous layer, the filler having a median particle size of 100 micrometers to 1000 micrometers and a median particle size of 1 m 2 / g to 100m 2 and a non-uniform filler having a specific surface area of 100 / g; the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls; the non-uniform filler being agglomerated.
4. 1. An acoustic article comprising: A porous layer; A non-uniform filler received in the porous layer, the filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 micrometer to 10 micrometers. 2 / g~800m 2 and a heterogeneous filler comprising diatomaceous earth, vegetable-based filler, unexpanded graphite, polyolefin foam, or a combination thereof, having a specific surface area of 100 nm to 100 nm / g; the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls; the non-uniform filler being agglomerated.
5. The acoustic article of any one of claims 1 to 4, wherein the non-uniform filler has a Dv50 / Dv90 particle size ratio of 0.25 to 1.
6. The acoustic article of any one of claims 1 to 5, wherein the porous layer comprises a nonwoven fibrous layer having a plurality of fibers.
7. 1. A method of making an acoustic article, comprising the steps of: Directly forming a nonwoven fibrous web; delivering a non-uniform filler to the non-woven fibrous web as the non-woven fibrous web is directly formed, the non-uniform filler having a median particle size of 1 micrometer to 1000 micrometers and a median particle size of 0.1 micrometer to 1 micrometer; 2 / g~800m 2 and delivering a diatomaceous earth, a plant-based filler, unexpanded graphite, a polyolefin foam, or a combination thereof, having a specific surface area of about 100 nm to about 100 nm; the acoustic article has a flow resistance of 100 MKS Rayls to 8000 MKS Rayls; The method wherein said heterogeneous filler is agglomerated.
8. A method of using the acoustic article of any one of claims 1 to 6, comprising placing the acoustic article proximate to a surface to damp vibrations of the surface.
9. 7. A method of using the acoustic article of any one of claims 1 to 6, comprising placing the acoustic article in proximity to an air cavity to absorb sound energy transmitted through the air cavity.
Citation Information
Patent Citations
Sound absorption material
JP2019044548A
Acoustic ceiling board with improved aesthetics
WO2015175733A1
Sound attenuation
WO2015193671A1